National expert group technical consultation on prevention and treatment of iron deficiency anemia - Sachdev, H PS; Kurpad, Anura; Saxena, Renu; Kapil, Umesh (Indian Journal of Community Health, 2018)
A “National Expert Group Technical Consultation on Prevention and Treatment of Iron Deficiency Anemia” was held from 23rd to 24th April 2018 at All India Institute of Medical Sciences, New Delhi. The Consultation was conducted under the aegis of Ministry of Health and Family Welfare, Government of India. The following were the Co-organizers i) Departments of Human Nutrition and Hematology, All India Institute of Medical Sciences, New Delhi; ii) Sitaram Bhartia Institute of Science and Research (SBISR), New Delhi; iii) Public Health Foundation of India (PHFI), iv) Nutrition Society of India (NSI), v) Indian Association of Preventive and Social Medicine (IAPSM), vi) Indian Academy of Pediatrics (IAP) Nutrition Sub-specialty Chapter , vii) Federation of Obstetric and Gynecological Societies of India (FOGSI), viii) Indian Public Health Association (IPHA), ix) Indian Society of Haematology and Blood Transfusion (ISHBT), x) International Epidemiological Association - South East Asia Region (IEA-SEA), xi) Alive and Thrive India, xii) Knowledge Integration and Translational Platform (KnIT – BIRAC-DBT), and xiii) World Health Organization (WHO).